Benefits, Limits, and Risks of GPT-4 as an AI Chatbot for Medicine - Lee, Peter; Bubeck, Sebastien; Petro, Joseph (The New England journal of medicine, 2023)
Chatbots are computer programs with which one can have a conversation. In this article, the authors describe how the GPT-4 chatbot, which has been given a general education, could affect the practice of medicine.